Calidad del servicio y satisfacción de los usuarios del encanto de laguna, Iquitos 2024 - Rengifo Zuasnahabar, Jose Luis (2024)
In a recent study conducted at the tourist resort ‘El Encanto de Laguna’ in Iquitos during 2024, the relationship between service quality and customer satisfaction was investigated. The sample consisted of 30 customers who visited the customer service area. The results showed a Pearson correlation of 1.000, indicating a perfect relationship between service quality characteristics and customer satisfaction. Additionally, the hypothesis was confirmed when the P-value (significance) was less than 0.05. In summary, service quality is closely linked to customer satisfaction in this tourist establishment.